The Effect of ZEP Quiz on Critical Thinking Skills of Culinary Vocational School Students - Pandhu Wiseno Wahyu Aji; Lismi Animatul Chisbiyah; Erna Tungga Dewi (Universitas Muhammadiyah Mataram, 2026)
Abstract: The integration of gamification-based interactive media into vocational education has become increasingly critical as conventional instructional approaches continue to fall short in fostering higher-order thinking skills among Generation Z learners. The study aims to examine the impact of ZEP Quiz interactive learning media on the critical thinking skills. A Mixed Methods approach with Sequential Explanatory design was employed. Mixed Methods integrating quantitative data from pre-tests, post-tests, and questionnaires with qualitative data from classroom observations and in-depth interviews. Respondents comprised 33 Grade X Culinary students in the Basic Culinary subject, Even Semester 2025/2026. Results showed a mean pretest score of 58.2 rising to 79.6 posttest, with an average N-Gain of 0.51 (moderate category). The critical thinking questionnaire yielded 81.2% and student response questionnaire 83.7%, both in the excellent category. Qualitative findings revealed that ZEP Quiz's immediate feedback and point-based competition features significantly enhanced students' analytical and evaluative capacities. ZEP Quiz is concluded to be an effective learning medium for improving critical thinking skills in culinary education.Abstrak: Penelitian bertujuan mengkaji dampak penerapan media pembelajaran interaktif ZEP Quiz terhadap keterampilan berpikir kritis. Latar belakang penelitian didasari kondisi pembelajaran kuliner konvensional yang belum optimal dalam mendorong keterlibatan aktif dan pengembangan kemampuan kognitif tingkat tinggi siswa. Penelitian menggunakan pendekatan Mixed Methods dengan rancangan Sequential Explanatory. Mixed Methods mengintegrasikan data kuantitatif dari pretes, postes, dan kuesioner dengan data kualitatif dari observasi kelas dan wawancara mendalam. Responden 33 murid kelas X Program Keahlian Kuliner pada mata pelajaran Dasar-Dasar Kuliner, Semester Genap 2025/2026. Hasil rerata skor pretes 58,2 meningkat menjadi 79,6 pada postes, dengan rerata N-Gain 0,51 (sedang). Kuesioner keterampilan berpikir kritis menghasilkan persentase 81,2% dan kuesioner respons murid mencapai 83,7%, keduanya berkategori sangat baik. Temuan kualitatif mengungkap fitur umpan balik segera dan sistem kompetisi berbasis poin ZEP Quiz secara signifikan mendorong kapasitas analitis dan evaluatif siswa. Disimpulkan bahwa ZEP Quiz efektif dalam meningkatkan kemampuan berpikir kritis pada konteks pendidikan kuliner.